Probing the biocompatibility of biomedical interfaces using the Quartz Crystal Microbalance with Dissipation - Cromhout, Mary (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
The biomedical application of nanotechnology has come into the spotlight, with the promise of 'personalised' therapeutics that couple early diagnosis with targeted therapeutic activity. Due to the rapid growth of the biomedical applications of nanoparticles, along with the lack of understanding concerning their interactions with biomolecules, there is a pressing need for the development of standard methods directed at investigating the effect of introducing these unique particles into the human body. The central aim of this research is to establish a platform directed at assessing the biological fate of pioneering therapeutic particulate agents, such as metallophthalocyanines (MPcs) and multi-walled carbon nanotubes (FMWCNTs). In particular, we proposed, that Quartz Crystal Microbalance with Dissipation (QCM-D) technology may be employed to assess the composition of blood protein corona deposited on the therapeutic surface, and subsequently assess the biocompatibility of such particles. The proposed method of protein detection utilises the nanogram sensitivity of QCM-D technology to monitor highly specific antibody-antigen interactions. In particular those interactions which occur when probe antibodies are used to detect adsorbed blood proteins deposited on target particle-modified sensor surfaces. Protein detection analysis was directed toward identification of surface bound human serum albumin, complement factor C3c, and human plasma fibrinogen. Preliminary analysis of generic biomedical surfaces indicated human serum albumin demonstrates a higher binding affinity towards positively charged surfaces (i.e. cysteamine self-assembled monolayer), followed by hydrophobic surfaces. Detection of complement C3c, corresponded with literature, where lower levels were detected on negatively charged surfaces (i.e. mercapto undecanoic acid self-assembled monolayer), and higher levels of more hydrophobic surfaces (i.e. 11-amino undecane thiol self-assembled monolayer). Human plasma fibrinogen was observed to favour hydrophilic over hydrophobic self-assembled monolayer surfaces, which was in accordance with literature. Application of the proposed protein detection method for biocompatibility analysis of target therapeutic molecules, namely metallophthalocyanines and acid functionalised multi-walled carbon nanotubes, demonstrated a dependence on modified-surface film characteristics, such as surface charge and topography with regards to human serum albumin and human plasma fibrinogen analysis representing new insights into their potential biomolecular interactions The highest levels of detected human serum albumin and complement C3c were detected on the GePcSmix-modified surfaces. AlPcSmix-modified surfaces analysis suggested the highest levels of human plasma fibrinogen. Two methods of acid functionalisation were employed, using both nitric and sulphuric acid, and pure nitric acid. A general increase in detected human serum albumin, corresponding with an increase in functionalisation time, was observed. Complement C3c detection suggested an increase in deposited complement C3c, with increasing functionalisation time, when assessing nitric acid functionalised multi-walled carbon nanotubes, and a decrease, with increasing functionalisation time, when assessing nitric and sulphuric acid functionalised multi-walled carbon nanotubes. Analysis of human plasma fibrinogen was inconclusive, as were cytotoxicity experiments utilising MCF-7 cells in the presence of metallophthalocyanine complexes, raising simultaneously important considerations for their application and study. In the first such detailed examination of its kind it was concluded that the proposed method of protein detection, using QCM-D, allows for the rudimentary but rapid means of analysis of select protein corona deposited on particulate biomedical surfaces.
Keywords: Biomedical materials; Nanostructured materials; Biomedical engineering; Quartz crystal microbalances; Blood proteins; Nanoparticles